Nilai-Nilai Simbolik Dan Budaya Tarian Tebe Masyarakat Belu Nusa Tenggara Timur (NTT) - Maria Gundulfa Olo (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research with the title Symbolic values of tebe dance culture of the Belu community of East Nusa Tenggara (NTT), being a cultural nation strengthens the identity of symbolic values and tebe dance culture with character in maintaining the cultural symbol of adaat istaiadat with tebe dance, for values, norms and culture in social life. Character education in the family will be the foundation for the formation of the child's personality, which is a reflection of the character of the Indonesian people in society, the Indonesian nation. This method aims to find out the symbolic and cultural values of tebe belu dance, demonstrated by men and women holding hands while singing together chanting verses and rhymes containing praise, criticism or requests, while stomping their feet according to the rhythm of the song. To know the procession of tebe dances performed at Church events or other joyous events. Also the cooling ceremony of the traditional house (pemali house) or when stepping on rice, and the impact, preserving tebe belu dance. This research was conducted in nualain village, lamaknen sub-district, south of belu district, East Nusa Tenggara. The research method with a quantitative descriptive approach, as respondents are traditional leaders (village head, community and traditional elders) of the nualain village community of belu district, south lamaknen sub-district.